Fragmented Selves and the Politics of Memory Exploring Exile and Identity in Malika Oufkir's Freedom: The Story of My Second Life - IDMOULID, Omar (International Journal of Language and Literary Studies, 2025)
Autobiography has increasingly achieved access in literary and cultural scholarship bringing attention to the ways in which the self is perceived and (re)created in virtue of our memories. To investigate the interrelation between self and memory, this paper is engaged with the following questions: what do we mean by the self or himself (autos)? How memory is constituted in the self? How can the self be written into narrative? Can the self be explained by in terms of memory? By introducing the concept of the self on account of these questions, this paper hopes to show that self and memory are intertwined through the process of constructing stories we tell, share and/or conceal about ourselves and others. Within this ambit, this paper seeks to examine Malika Oufkir’s Freedom: The Story of My Second Life through the prism of exile, memory, and identity (re)construction. It investigates how this narrative navigates imprisonment, displacement and estrangement. Central to this analysis is the representation of memory as both a site of agony and a mechanism for resistance, through which Oufkir reclaims agency over her identity. In short, the paper also explores the intricate interplay between personal and political exile in the sense that it delves deep into how the author’s experiences reflect broader themes of imprisonment, displacement, fragmentation and estrangement in the postcolonial context. Drawing upon theories of autobiographical memory and collective identity, this paper examines how Oufkir’s narrative intertwines personal and collective histories, revealing the complex interplay between individual memories and broader socio-cultural contexts. In essence, this paper adopts an eclectic methodology to address the question of autobiographical construction of self and memory. As such, the paper focuses on the transformative role of exile in shaping Malika’s identity and memory. By situating Oufkir’s narrative within the framework of gendered resistance, this paper seeks to illustrate how she transcends the boundaries of imprisonment and exilic condition in order to reconstruct a sense of being and knowing in a place and time in a world that remains deeply fractured by cultural and historical divides. Eventually, the paper underscores Freedom as a powerful testament to the enduring struggle for selfhood in the face of dislocation and marginalization.